Control Blood Sugar Levels by Brisk Walking Method - Sriwahyuni Sriwahyuni; Junaidin Junaidin; Jamila Kasim; Noviyati Hamundu; Sri Darmawan (Journal of Ners and Midwifery, 2021)
Diabetes mellitus (DM) is a chronic disease, and specific treatments are needed in order to control blood glucose. In addition to pharmacological therapy, non-pharmacology therapy also takes an important role to control blood glucose levels and should be done regularly. Brisk walking is one example of physical activity which included in non-pharmacology therapy and can improve body expenditure. This activity can help DM patient to control their blood glucose level within the normal range. The physical activity of Brisk Walking, which is one type of exercise that can maintain blood sugar levels within the normal range, especially in people with Diabetes Mellitus. This study aimed to determine the effect of Brisk Walking on the blood glucose level of DM patients at Tamalenrea Health Center Makassar City. This study adopted a quasy experiment and a one-group pre-post test design. A total of 16 respondents were selected purposively based on the determined criteria. Data analysis of the difference of blood sugar level between the treatment and control was carried out by using the Spearman correlation test with SPSS version of 21. The difference was significant with the value of p < 0.05. The results showed that the physical activity of Brisk Walking could control blood sugar levels. Statistical analysis showed that the average blood sugar content was significantly lower in patients practicing Brisk Walking (blood sugar level <200 mg/dl)(176.06%) than the control (blood sugar level > 200 mg/dl) (218.81%). So it can be concluded that by doing physical activity Brisk Walking can control blood glucose levels.